A small caenagnathid tibia from the Horseshoe Canyon Formation (Maastrichtian): Implications for growth and lifestyle in oviraptorosaurs. (December 2018) - Funston, Gregory F.; Currie, Philip J.
Abstract: Caenagnathid elements are exceptionally rare in the Horseshoe Canyon Formation (HCF), and a small tibia constitutes only the fourth record from the formation. The tibia is elongate and gracile, with a semi-circular cross-section. A representative survey of Late Cretaceous, North American theropod tibiae suggests that cross-sectional shape can be useful for distinguishing theropod superfamilies. Caenagnathid tibiae can be distinguished from those of other theropods by the combination of their elongation, semi-circular cross-sections, and absence of extensive contact between the fibula and distal ends of the tibia. Histological sections reveal that the individual represented by the tibia was likely just over one year old and was increasing its growth rate at the time of death. However, the cyclical growth mark is unusual, consisting of a zone of parallel-fibered bone, rather than a distinct line of arrested growth—similar to annuli of rapidly-growing young ornithischians. A transition in vasculature orientation and osteocyte lacunae size and density prior to the growth mark may represent a physiological change within the first year of life. It is possible that this represents fledging, ontogenetic niche shift, or an environmental change, but more evidence from other individuals is required to test this. The presence of endosteal lamellae suggests that the tibia already experienced significant mechanical loads, despite the young age of the individual. Together with evidence from other caenagnathids, it suggests that they were active early in life, consistent with a precocial lifestyle.